Analisis konsep Maqamat dalam Teosofi: Taubat, sabar, syukur, khauf, dan raja’ - Agustina, Eliza; Madjid, Findiah Farah Syafira; Raharjo, Maharani Kartika Chandra Kirana; Salsabila, Najwa Felaha; Faisol, Faisol (Maliki Interdisciplinary Journal, 2024)
This research aims to analyze the stations of theosophy, especially the stations of repentance, patience, gratitude, khauf, and raja'. This research uses the literature review method, which involves analyzing various literature from several sources to synthesize it into meaningful conclusions and generate new ideas. The results of the research show that in Sufism, maqamat is the position of a servant in the sight of Allah which is achieved through serious efforts in carrying out riyadhah, worship and mujahadah. In conclusion, maqamat and ahwal complement each other in a Sufi's spiritual journey, helping them achieve the ultimate goal of Sufism, namely makrifatullah or deep self-knowledge of Allah, with consistent practice in meditation, prayer, and self-reflection will help deepen spiritual understanding and experience in every maqam. The suggestion from this research is the importance of increasing understanding and awareness of the spiritual journey in achieving maqamat in theosophy. The implication is that a deeper understanding of maqamat and ahwal can help individuals to develop a closer relationship with Allah SWT and produce a more spiritually meaningful life.